Competence to restart meiosis of oocytes from different follicle sizes obtained from slaughterhouse ovaries - Ayala, Luis Eduardo (2019)
The competence of oocytes according to follicle size to restart meiosis was evaluated. The follicles were measured and classified as Group 1 (G1 <4 mm), Group 2 (G2 4-8 mm) and Group 3 (G3 >8 mm). The aspiration was performed by group with a 21G needle connected to a vacuum pump, with a pressure of 65 mmHg. The complex oocyte clusters (COCs) recovered were classified as suitable and unsuitable to produce embryos in vitro, according to the characteristics of the cumulus and the cytoplasm. Eligible and unsuitable COCs were assessed with the Brilliant Cresyl Blue (BCB) and were classified into BCB+ and BCB-. In vitro maturation (IVM) was carried out in microdroplets, incubated in a 5% CO2 chamber, 38.5 °C and 90% humidity for 24 hours. The meiotic progression was determined by extrusion of the polar corpuscle by epifluorescence under an inverted microscope. Oocyte morphometry was established using a high definition camera (Excelis AU-600-HD) and software (AmScope v.3.7). The recovery percentage of oocytes was greater than 63%. The G2 follicles provided a higher percentage of eligible COCs (65.7%), where 59% of this group was classified as BCB+. The fit oocytes of G1 and G2 resumed meiosis by 75%. In addition, it was observed that oocytes after IVM reduced their diameter. It is concluded that follicle oocytes between 4-8 mm (G2) provide a higher percentage of mature COCs; however, 50% of follicles <4 mm (G1) are a promising source of viable oocytes, so they should be used for in vitro embryo production.